Aktivitas Mahasiswa pada Media Sosial dan Tingkat Literasinya Tentang Undang-Undang Interaksi & Transaksi Elektronik - Gushevinalty Gushevinalty; Lely Arrianie (Postgraduate of Jayabaya University, 2016)
The purpose of this study is on the activities of students of the Faculty of Social and Political Sciences, Universit y of Bengkulu on social media,especially activity that leads to acts of c yber-bull ying. Furthermore, to ex plore the level of literacy of stud ents Oil legislation Interaction and Electronic Transactions (U U ITE ) governing ethics in social media. This study used a qualitative research approach. So that the data collecting technique is interview and observation as well as questionnaires o pen. lJZ formant s in this study were stud ent s of the Faculty of Social and Political S ciwces, University of Bengkulu who actively use social media. The results sl w<t•ed that the activity of stud ent s on social media uery much and epery student has a social media account for more than three accounts. Generally, the studwts explained that the post status activity in social medir. does not .1lways contai11 c yl1er bullying, lmt students are not denied ever did as 1.uell . Generall y, the l evel of literacy of stud ents at UU ITE is ver y low it is pnrved they do not know even do not understand the law.